Appliance of Innovative Technologies in Managerial Accounting Models in Digitalized Accounting System - Roupska, Teodora; Jolovski, James (Research Papers, 2022)
Since the end of the 20th century, high technologies have been dynamically introduced in the accounting practice. The process of digitalization of accounting systems is intensive and its scope is rather wide. However, the use of management accounting models requires a different approach in the generation, processing and analysis of information compared to that traditionally applied in financial accounting. The use of modern technologies in management accounting creates conditions to increase the efficiency and effectiveness in providing information required to meet the needs of the management. The main goal of the study is to evaluate the degree of application of these technologies and to assess the attitudes towards them in the Bulgarian practice, based on their advantages, identified by the authors. Several research methods have been applied for its implementation. Information provided through a desk research was analyzed. It is presented in summary of some of the most innovative technologies that greatly influence the accounting system. The benefits of modern technologies are evaluated, and opportunities for their application are proposed. A survey was conducted and empirical data on their use in the practice was analyzed.
Keywords: Integrated information systems; Enterprise resource planning; Character recognition; Machine learning; Artificial intelligence; Big data; Theory of constraints